Throughput Performance Analysis of Asynchronous Optical CDMA Networks With Channel Load Sensing Protocol - Maw-Yang Liu; Ting-Lin Wang; Shu-Ming Tseng (IEEE Photonics Journal)
In this paper, we propose a channel load sensing protocol (CLSP) to prevent the throughput decrease at heavy traffic conditions in asynchronous optical code-division multiple-access (CDMA) networks. The multiple access-interference (MAI) and beat noise are considered the main deleterious source of the network in addition to thermal, shot, and relative intensity noises. Moreover, we employ optical hard limiters and error correction codes to mitigate the physical channel impairments. However, the packet throughput performance declines severely when the number of active users reaches a certain amount in the network. We employ the proposed CLSP with optimum threshold that successfully mitigates the throughput reduction at heavy load conditions. Numerical results show that the proposed protocol can support a throughput rate above 100 Gb/s, which might be compatible for an eventual standardization for broadband optical access networks.